Sufism : the formative period - Karamustafa, Ahmet T., 1956- (New Edinburgh Islamic surveys., 2007)
This book is a comprehensive historical overview of the formative period of Sufism, the major mystical tradition in Islam, from the ninth to the twelfth century CE. Based on a fresh reading of the primary sources and integrating the findings of recent scholarship on the subject, the author presents a unified narrative of Sufism's historical development within an innovative analytical framework. Karamustafa gives a new account of the emergence of mystical currents in Islam during the ninth century and traces the rapid spread of Iraq-based Sufism to other regions of the Islamic world and its fusion with indigenous mystical movements elsewhere, most notably the Mal?matiyya of northeastern Iran. He analyses extensively the formation of Sufi communities, the imbrication of Sufi sainthood with popular saints' cults as well as nonconformist dimensions of Sufism and fully explicates the reasons for the increasing social prominence of the Sufi mode of piety during this early period in Islamic history. Key Features Strikes a balance between social and intellectual history Identifies and articulates questions of interest to scholars, students and general readers Consistently locates Sufism within its broader social and intellectual context